Jubilee - Giff, Patricia Reilly (Wendy Lamb Books, 2016)
"Judith stopped talking long ago when Mom left her in the care of beloved Aunt Cora. Going back into a regular fifth-grade classroom won't be easy, but she has her Dog and new friend who will help her through"--